2013
DOI: 10.1007/s10815-013-9987-z
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin ameliorates heat stress-induced impairment of blastocyst development In Vitro: –astaxanthin colocalization with and action on mitochondria–

Abstract: Purpose The effects of astaxanthin (Ax) on the in vitro development of bovine embryos cultured under heat stress were investigated in combination with the assessment of its cellular accumulation and action on mitochondrial membrane potential (Δ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 56 publications
3
33
0
Order By: Relevance
“…AST can diminish oxidative stress and maintain the integrity of mitochondria, as well as sustain mitochondrial function, protecting their redox balance [47]. In addition, it was shown that AST significantly decreases physiologically-arising oxidative stress and maintains mitochondria in a more reduced state even after stimulation with H 2 O 2 ; it prevents a drop in membrane potential and increases oxygen consumption by mitochondria [48,49]. Park and coauthors showed that AST treatment increased the mitochondrial content, ATP production, and activity of respiratory chain complexes [50].…”
Section: Discussionmentioning
confidence: 99%
“…AST can diminish oxidative stress and maintain the integrity of mitochondria, as well as sustain mitochondrial function, protecting their redox balance [47]. In addition, it was shown that AST significantly decreases physiologically-arising oxidative stress and maintains mitochondria in a more reduced state even after stimulation with H 2 O 2 ; it prevents a drop in membrane potential and increases oxygen consumption by mitochondria [48,49]. Park and coauthors showed that AST treatment increased the mitochondrial content, ATP production, and activity of respiratory chain complexes [50].…”
Section: Discussionmentioning
confidence: 99%
“…Development to the blastocyst stage was not compromised in bovine embryos > 8‐cell stage subjected to 40.5°C for 10 hr on Day 4 after insemination. In contrast, exposure to the same heat shock on Days 4 and 5 after insemination reduced blastocyst development from 40.6% in the control group to 21.5% in the heat‐shocked group (Kuroki et al, ). Exposure of 8‐cell embryos to 41°C for 6 hr reduced the proportion of embryos that reached the blastocyst stage (Sakatani, Yamanaka, Kobayashi, & Takahashi, ).…”
Section: Effect Of Heat Stress On Embryonic Developmentmentioning
confidence: 99%
“…HS produces excessive ROS, induces apoptosis, and/or reduces the mitochondrial membrane potential in bovine oocytes (Soto and Smith, 2009). In an effort to reduce the oxidative stress in oocytes associated with hyperthermia, using of antioxidants such as folic acid (Koyama et al, 2012), purple sweet potato anthocyanins (Sakatani et al, 2007), Astaxanthin, acarotenoid substance, added to the embryo culture medium (Kuroki et al, 2013), and in vivo administration of antioxidant epigallocatechin gallate significantly improved the blastocyst formation rate and decreased the ROS levels of the heat-shocked embryos. Heat-induced oocyte DNA fragmentation (TUNEL positive) can also be reversed by supplementation of IVM medium with apoptotic cascade inhibitor agents (Roth and Hansen, 2004a), sphingosine 1-phosphate (Roth and Hansen, 2004b), or a BH4 peptide (Soto and Smith, 2009).…”
Section: Heat Stressmentioning
confidence: 99%